Endodontic management of maxillary first molar with atypical canal morphology: Report of three cases - Osama Adeel Khan Sherwani; Bhumika Kapoor; Rajat Sharma; Surendra Kumar Mishra (Wolters Kluwer Medknow Publications, 2016)
Maxillary first molar with three roots and 3-4 canals is a common occurrence. However, extreme variations in their canal morphology have been reported ranging from one single canal and one root to as many as eight root canals. This article presents three cases of successful endodontic management of maxillary first molars with atypical canal morphologies, thus highlighting the fact that variations do occur and an endodontist should always be aware of aberrancies in root canal system apart from the knowledge of normal root canal anatomy.